Prognostic value of cough force measured by peak expiratory flow in a 4-year longitudinal cohort study of geriatric patients with oropharyngeal dysphagia - Stoev, Kiril; Wirth, Rainer; Labeit, Bendix; Muhle, Paul; Suntrup-Krueger, Sonja; Dziewas, Rainer; Lueg, Gero; Trampisch, Ulrike Sonja; Pourhassan, Maryam (Frontiers in Aging, 2025)
Introduction and objectiveOropharyngeal dysphagia (OD) is a potentially life-threatening disorder of the swallowing process that may significantly impair a patient’s prognosis and quality of life. This study aimed to investigate the association between cough force (measured by peak expiratory flow) and pneumonia incidence in older hospitalized patients with OD and to assess the relationship between peak flow, dysphagia severity and mortality over a 4-year follow-up period.MethodsIn this retrospectively longitudinal cohort study, OD was evaluated using flexible endoscopic examination of swallowing (FEES). Patients with suspected OD underwent Peak Flow (PF) measurement prior to initiation of FEES. Follow-up data were collected on pneumonia incidence, episodes, and patient survival via telephone surveys. Cox regression models, adjusted for potential confounding variables such as age and gender, were used to explore the relationship between pneumonia incidence, PF and dysphagia severity.ResultsAmong 98 patients (mean age 80.4 ± 8.2 years, 67% male), the median PEF was 220 L/min (IQR 150–300). Post-discharge, 38% developed pneumonia—11% had one episode and 27% had multiple episodes. Dysphagia severity was mild in 40%, moderate in 40%, and severe in 20% of patients. Over an average follow-up of 1,334 days (3.7 years), the mortality rate was 64%. Patients with lower PF experienced a significantly higher risk of developing pneumonia compared to those with higher PF (p = 0.030). Patients with severe dysphagia had a substantially lower survival rate compared to those with light or moderate dysphagia, as demonstrated by the Cox-models.ConclusionReduced cough force as measured by peak expiratory flow was significantly associated with an increased risk of pneumonia in older hospitalized patients with OD.